1995
DOI: 10.1128/jcm.33.2.455-457.1995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ligase chain reaction for use with urine for identification of Neisseria gonorrhoeae in females attending a sexually transmitted disease clinic

Abstract: The high sensitivity of nucleic acid amplification tests such as ligase chain reaction (LCR) has the potential to simplify specimen collection for the microbiologic diagnosis of gonorrhea. We screened first-void urine specimens from 283 women attending a Birmingham, Ala., sexually transmitted disease (STD) clinic by using LCR and compared the results to those of cervical and urethral cultures for gonorrhea diagnosis. Fifty-three (18.7%) women had positive cervical cultures for gonorrhea, and 41 of the 53 (77%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(41 citation statements)
references
References 9 publications
3
37
0
1
Order By: Relevance
“…1 All major health policy organizations recommend annual chlamydial screening for sexually active adolescent females. [2][3][4] The nucleic acid amplification technique applied to urine samples provides a sensitive noninvasive method to screen adolescents for Chlamydia trachomatis and Neisseria gonorrhoeae [5][6] and are more cost-effective compared with pelvic examinations. 7 Recently, self-collected vaginal swab tests have been successfully implemented as another method of obtaining sexually transmitted disease (STD) specimens from adolescent and adult women, [8][9][10] although this technique awaits approval by the Food and Drug Administration (Rockville, Md).…”
mentioning
confidence: 99%
“…1 All major health policy organizations recommend annual chlamydial screening for sexually active adolescent females. [2][3][4] The nucleic acid amplification technique applied to urine samples provides a sensitive noninvasive method to screen adolescents for Chlamydia trachomatis and Neisseria gonorrhoeae [5][6] and are more cost-effective compared with pelvic examinations. 7 Recently, self-collected vaginal swab tests have been successfully implemented as another method of obtaining sexually transmitted disease (STD) specimens from adolescent and adult women, [8][9][10] although this technique awaits approval by the Food and Drug Administration (Rockville, Md).…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that molecular amplification assays such as PCR and ligase chain reaction (LCR) have high sensitivity and specificity for detection of either gonorrhea or chlamydia in a variety of sample types including urethral and endocervical swabs and urine (2,7,11,16,17,19,21,22). However, they require separate processing and ampli-fication techniques for each pathogen.…”
mentioning
confidence: 99%
“…Besides endocervical specimens, female urine can be also be used for the detection of C. trachomatis by PCR-or LCR-based assays (1,2,4,13,16,18,19,21,23). An LCR-based assay for the detection of Neisseria gonorrhoeae in female urine specimens has also been described (6,24). The use of these highly sensitive tests has prompted the adoption of an expanded "gold standard" to compare the assay results obtained with specimens collected from different sites of infection (15,18).…”
mentioning
confidence: 99%